Allogeneic fibroblasts vs conventional debridement after successful endovascular interventions for treating chronic ulcers induced by peripheral artery disease - Bazylbek Zhakiyev; Didar Khassenov; Gulnara Sakhipova; Natalya Zagorulya; Gaukhar Kuanyshbayeva; Nurlan Zhampeissov; Damir Biktashev; Murat Jakanov; Ainur Donayeva; Ibrahim A. Abdelazim (Videosurgery and Other Miniinvasive Techniques)
Introduction: Fibroblasts are stromal and connective tissue cells that play crucial roles in the intracellular matrix and granulation tissue synthesis during tissue proliferation. They are also responsible for epithelialization and healing of skin lesions.